2017
DOI: 10.3390/molecules22111957
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Toothpaste Containing Australian Melaleuca alternifolia Oil and Ethanolic Extract of Polish Propolis on Oral Hygiene and Microbiome in Patients Requiring Conservative Procedures

Abstract: The study was based on the use of a toothpaste with antiphlogistic activity, containing Australian Melaleuca alternifolia oil (tea tree oil—TTO) and ethanolic extract of Polish propolis (EEP). Fifty-one patients with varying conditions of the gingiva were divided into two groups. The study group received the toothpaste with TTO and EEP, while the control group received the same toothpaste but without TTO and EEP. Approximal plaque index (API), simplified oral hygiene index (OHI-s) and modified sulcus bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
2
19
0
7
Order By: Relevance
“…Antimicrobial agents such as chlorhexidine mouthwash, (21) toothpaste containing thiocyanate and carbamide peroxide, (17) and toothpaste containing propolis, (15,16) can influence periodontal disease parameters, such as gingivitis and gingival bleeding, and oral hygiene, which is in line with the results of the present study, indicating that Ardox-X active oxygen can reduce gingival bleeding. Fernandez Y Mostajo et al investigated the antimicrobial potential of Ardox-X active oxygen in the form of mouthwash on oral bacteria and dental plaque.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Antimicrobial agents such as chlorhexidine mouthwash, (21) toothpaste containing thiocyanate and carbamide peroxide, (17) and toothpaste containing propolis, (15,16) can influence periodontal disease parameters, such as gingivitis and gingival bleeding, and oral hygiene, which is in line with the results of the present study, indicating that Ardox-X active oxygen can reduce gingival bleeding. Fernandez Y Mostajo et al investigated the antimicrobial potential of Ardox-X active oxygen in the form of mouthwash on oral bacteria and dental plaque.…”
Section: Discussionsupporting
confidence: 90%
“…(12)(13)(14) Previous studies have shown that toothpastes containing therapeutic agents, such as propolis, thiocyanate, and carbamide peroxide, can be effective in improving periodontal parameters such as reducing gingival bleeding. (15)(16)(17) Another substance that can be used as a prophylactic and therapeutic agent for implant hygiene is active oxygen with Ardox-X technology. Ardox-X, as an auxiliary active substance in mouthwashes, has been effective in the treatment and prevention of periodontitis and peri-implantitis.…”
mentioning
confidence: 99%
“…It was found that Sudanese students had lower caries prevalence than Iraqi students. [ 27 30 ] This finding was similar to that of a study conducted in children from Saudi Arabia between ages 13 and 15 years and Western countries. [ 31 32 33 ]…”
Section: Discussionsupporting
confidence: 87%
“…While the possibility of performing a quantitative analysis of the different parameters measured in the studies was considered, it was only possible to carry out the meta-analysis of probing depth assessment. Regarding the rest of the parameters assessed in the studies, the Oral Hygiene Index (OHI) was evaluated in 2 of the studies [ 24 , 25 ] and the Gingival Index (GI) in another 2 [ 25 , 28 ]. Although gingival bleeding was measured in most of the studies, it was tested using different indices depending on the study, which created a disparity of clinical criteria for assessment and precluded the unification of data [ 21 , 22 , 23 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although gingival bleeding was measured in most of the studies, it was tested using different indices depending on the study, which created a disparity of clinical criteria for assessment and precluded the unification of data [ 21 , 22 , 23 , 26 , 27 , 28 ]. As for plaque control, 4 studies tested it using the Plaque Index (PI) [ 23 , 24 , 25 , 26 ], although 2 of them [ 25 , 26 ] did not provide numerical data. Concerning clinical attachment level, although it was measured in 3 of the studies [ 21 , 22 , 28 ], that by Sparabombe and colleagues [ 22 ] did not explain the measurement criterion, which means that it was discordant with the measurement units used in the other 2 studies.…”
Section: Methodsmentioning
confidence: 99%